Evaluation of Serum Interleukin-17F Levels in Asthmatic Patients: a Case-Control Study in Baghdad, Iraq - Atta, Rafal Yahya; Ghali, Zafir Hassan (American Journal of Biology and Natural Sciences, 2025)
This case-control study evaluates serum levels of IL-17f among Iraqi patients with asthma . The study involved 80 participants, including 45 asthmatic patients and 35 healthy controls, The mean age was 30±7.91 years for patients and 34.67±8.71 years for controls. Serum IL-17F levels were measured using ELISA (enzyme-linked immunosorbent assay) .Serum IL-17F levels were significantly higher in asthma patients compared to controls (41.45±8.64 vs. 21.63±0.66 ng/mL; P= 0.05). Among asthma patients, males exhibited significantly higher IL-17F levels than females (59.53±15.39 vs. 24.80±1.01 ng/mL; P= 0.02).